Curso técnico em segurança do trabalho no Instituto Federal de Educação, Ciência e Tecnologia de Pernambuco : antecedentes e condicionantes de sua recente expansão - Silva, Eraldo Alves da (2011)
In recent years, the economy of Pernambuco has reversed its historical process of industrial disruption occurred in the nineties, currently going through a phase of fast industry growth, which main change agent is the creation of the Suape Port Industrial Complex. With this growth rhythm in education, specifically in the medium level technical education, various public and private educational institutions appeared in the State, because of the increased demand and valuation of technical education. In Federal Institute of Education, Science and Technology of Pernambuco (IFPE), institution that for over 100 years has been acting in technical education in the state, there was a peculiar phenomenon, base of this research, with the increase in demand for technical formation, mainly the Work Safety Technical course, over the courses traditionally more competitive. The main objective of this study was to understand the factors that influenced the expansion in demand of the Technical Work Safety course at IFPE in recent years, having as specific objectives the identification in IFPE vestibular of the candidates quantitative that opted for the Work Safety course, the verification of the industrial growth occurred in the Suape Port Industrial Complex and the analysis of reasons for the choice of Work Safety Technical course in IFPE, against other technical formation offered by this institution. The starting point were the hypotheses that the increased demand for this course was due to industrial growth occurred in the State, the diversification of enterprises types implanted and to bigger visibility of the Work Safety Technical profession, due to the increase of job offer number presented to media. The research method used was the case study, having as locus the campus Ipojuca of IFPE and as participants in research the students of the Work Safety Technical course, institutional management and human resources companies areas in the region. The results obtained by the application of questionnaires to surveyed, were confronted with the hypotheses, showing that among the factors that influenced the search for the Work Safety Technical course the diversity of economic sectors in which the individual can act and Suape industrial growth are highlighted. It is our intent that the results obtained in this work serve as an instrument of reflection for teachers of technical education and allows the taking of actions aiming the improvement in teaching quality and overcoming inequalities.